2017
DOI: 10.1007/s11011-017-9971-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel frameshift mutation in the sterol 27-hydroxylase gene in an Egyptian family with cerebrotendinous xanthomatosis without cataract

Abstract: Cerebrotendinous xanthomatosis (CTX) is a rare autosomal recessive lipid storage disorder caused by deficiency of the mitochondrial cytochrome P450 sterol 27-hydroxylase enzyme encoded by CYP27A1 gene. CTX is characterized by tendon xanthomas, juvenile cataracts and multiple progressive neurological symptoms. Here we report on the clinical and molecular findings of a 35-years old Egyptian patient with CTX without cataract. Parents were first cousins with family history of two deceased sibs with mild impaired c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Childhood diarrhea and juvenile cataracts are the primary non-nervous system manifestations[ 5 ]. However, Abdel-Hamid et al [ 6 ] reported a case of CTX with tendon xanthomatosis and neurological impairment without obvious cataracts. Brain MRI typically reveals symmetrical lesions in the cerebellar white matter, especially the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood diarrhea and juvenile cataracts are the primary non-nervous system manifestations[ 5 ]. However, Abdel-Hamid et al [ 6 ] reported a case of CTX with tendon xanthomatosis and neurological impairment without obvious cataracts. Brain MRI typically reveals symmetrical lesions in the cerebellar white matter, especially the cerebellum.…”
Section: Discussionmentioning
confidence: 99%